Social worker assistance (analytical study of ex-commercial sex workers) in PPSKW Makassar - Syamsuddin. AB (Technium Social Sciences Journal, 2021)
This study aims to analyze the form of mentoring role performed by social workers towards former commercial sex workers, both during pre, admission, post at the Mattirodeceng Women’s Social Service Center (PPSKW). This type of qualitative descriptive research with data sources of 8 informants. Data obtained through observation, in-depth interviews and documentation, then analyzed by data reduction, data presentation, and drawing conclusions and analyzing the structural functionalism theory approach. The results showed that the assistance provided by social workers to former commercial sex workers was: a). Acting as a client recipient who of course does the assessment earlier, b). Acts as a motive for the clients to the problems faced in order to have a zest for life, c). As an advocacy and a coalition of related officers, d). Physical coaching through exercise, as well as providing consumption for clients, d) Providing skills guidance both in culinary, clothing and sewing courses, e). Act as spiritual guide.